2018
DOI: 10.1371/journal.pone.0202041
|View full text |Cite
|
Sign up to set email alerts
|

Patching a leak in an R1 university gateway STEM course

Abstract: A cognitively intensive companion service course has been introduced to the main fall general chemistry class at Cornell University. For years 2015 and 2016, priority students (those from groups under-represented and economically disadvantaged) show respectively improvement of +0.67 and +0.51 standard deviations in final course grade compared to priority students not in the program. Non-priority students show respectively a +0.66 and +0.62 standard deviation improvement. Progressive improvement (as measured by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…As noted above, the active learning methods employed in this and similar studies also provides students with a learning community, so we conclude that active learning alone is not responsible for narrowing gaps. The Treisman paradigm requires a sizeable time commitment from students and educators alike; while this is a potential roadblock, as many URM and firstgeneration students have jobs and other time commitments that can prevent them from participating in ESP, this time commitment is also partly responsible for creating the cohesive learning community (Lee et al, 2018). Theobald et al (2020) results highlight the interaction of active learning and community in positive results.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…As noted above, the active learning methods employed in this and similar studies also provides students with a learning community, so we conclude that active learning alone is not responsible for narrowing gaps. The Treisman paradigm requires a sizeable time commitment from students and educators alike; while this is a potential roadblock, as many URM and firstgeneration students have jobs and other time commitments that can prevent them from participating in ESP, this time commitment is also partly responsible for creating the cohesive learning community (Lee et al, 2018). Theobald et al (2020) results highlight the interaction of active learning and community in positive results.…”
Section: Discussionmentioning
confidence: 98%
“…The sustained access to these environments builds agency and identity for students within mathematics and other disciplines, supporting the persistence needed for long-term success in these disciplines. Forty years ago, Treisman's ESP methods (Asera, 2001) showed that URM students could achieve grade distributions equal to or greater than the class as a whole (15 ± 20), while more recent studies show that if his methods are not diluted, the results are equally positive (Lee et al, 2018;Theobald et al, 2020). Therefore, results from this study and others support calls to replace traditional lecture with evidencebased, active-learning course designs across STEM disciplines and that these innovative in instructional strategies can increase equity in higher education.…”
Section: Discussionmentioning
confidence: 99%
“…The general chemistry sequence is often referred to as a "gateway" to careers in STEM due to the standard requirement that STEM majors complete these courses. However, research suggests that this gateway is often a barrier to careers in science for many students (Lee et al, 2018;Redmond-Sanogo et al, 2016;Robinson et al, 2019;Witteveen & Attewell, 2020). Despite calls for reform spanning over a decade (Next Generation Science Standards [NGSS] Lead States, 2013; President's Council of Advisors on Science and Technology, 2012), and considerable increases in what is known about how people learn (National Academies of Sciences, Engineering, and Medicine et al, 2018;National Research Council, 2000, 2001 widespread improvements in general chemistry learning environments have not been forthcoming (Lund & Stains, 2015;Matz et al, 2018;Popova et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In some cases, SI resulted in improved grades for all students [ 1 ], and in other cases, disproportionately benefited underrepresented students [ 2 ]. SI courses taught by instructors or graduate TAs [ 3 , 4 ], as well as courses lead by undergraduate “peers” of enrolled students [ 5 – 10 ] have been shown to have a substantial impact in chemistry. Despite the popularity of SI in other disciplines, we could find no published studies in the physics education literature documenting the effects of SI courses, though there exist SI courses in physics and some more general studies suggesting positive benefits of such courses in physics [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%